Elaboration of an Analytical Formula for the Calculation of the Surface Temperature - Abdelhamid Mammeri; Mostefa Lallam (Civil Engineering Journal, 2019)
Pavement structures are sometimes subject to repeated dimensional variations of thermal origin generating mechanical stresses that may be detrimental to their durability. Among the most frequently observed degradations, by these stress, are the transverse cracks whose frequency, depth, and variable openings reduce the ride comfort. In this context, where such solicitations are preponderant and the strong variation is noticed on the surface, an analytical approach for calculating the surface temperature of a flexible pavement has been proposed. This approach is able to deal with the transient thermal problem including the phenomenon of ambient temperature and the influx of solar flux specifically for arid regions where the sky is often clear. This approach is adopted because it proposes a simplified calculation of the surface temperature. The model was built on a database measured on the experimental pavement of the laboratory of Egletons GEMH (France), using the calculation code Eureqa formulate. Although neglected in the domain's literature, the meteorological parameters (air temperature and solar flux) are taken into consideration in the analytic function because they give good prediction. The model has practical meanings to predicting the maximum, minimum, and amplitude of the pavement surface temperature. Hence, a good surface temperature assessment provides a key factor for further thermal cracking modeling.